Revitalization of the Mandailing Regional Language (North Sumatra, Indonesia); Focusing on Metaphor Mapping and Concrete Efforts for Language Preservation - Surip, M; Dalimunthe, Syairal Fahmy; Sumarsono; Rohim, Syaiful; Pulungan, Hendra Kurnia (Universitas Muhammadiyah Malang, 2024)
The background of writing this paper is based on a sense of concern about the extinction of the Mandailing regional language, especially the metaphor type. The purpose of this research is to reveal the pattern of mapping metaphors of the Mandailing regional language and concrete efforts in the preservation and revitalization of the Mandailing regional language to avoid extinction. The data source used is the use of the Mandailing regional language, a metaphor type used in social communication in the community. The data of this study is in the form of lingual units of spoken language in the social life of metaphor-type communities. The research method uses qualitative descriptive with data collection through the interactive engagement method. Meanwhile, the data processing method is based on the analysis of CMT conceptual metaphor theory through the mapping of various domains referred to in the use of metaphor-type Mandailing regional language. The data analysis method uses the referential method, to show and compare references or meanings contained in the realm of metaphorical speech mapping. This study found that there are five domains used in the metaphorical type of Mandaling regional language, namely: the human realm 5 (25 %) data, the object realm 4 (25 %) data, the plant realm 3 (18.75 %) data, the earth realm 2 (12.5 %) data, and the living realm 3 (18.75 %) data. These five realms of metaphors are used as referential data in metaphorical speech for society through the association of relevant meanings in social life. Meanwhile, the data on the language attitudes of the Mandailing people is still considered inadequate, and the level of community concern in preserving the Mandailing language is not good. Based on data on the level of public concern from cultural practitioners 8%, educators/teachers 20%, and the general public 26%. There are several concrete efforts in revitalizing the Mandailing regional language, including: the need for special regional regulations to strengthen and preserve, changing school curriculum policies by including the content of the Mandailing regional language, increasing community involvement in the preservation of regional languages, making the Mandailing regional language an active language of daily communication in the community.